2020
DOI: 10.1016/j.heliyon.2020.e04847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of procyanidins on lipid metabolism and inflammation in rats exposed to alcohol and iron

Abstract: Background Lifestyle involving uncontrolled alcohol consumption coupled regularly with red meat and other iron sources has detrimental effects on the liver, which in the long term, results in Alcoholic Liver Disease (ALD). Procyanidin has lately garnered increasing attention and has become the focus of research owing to its antioxidant properties. This study explores the anti-inflammatory effects of procyanidins, in preventing ALD, by analyzing the biological activities of the compound on liver in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Rats in the CON group were fed normal feed, while rats in the other four groups were fed a high-fat diet for 8 continuous weeks. The design of HPC dosage was referred to the previous research studies of Gao et al 30 and Lobo et al 31 Meanwhile, rats in the L-HPC, M-HPC and H-HPC groups were orally given 50, 100 and 200 mg per kg bw of HPC for 8 weeks, respectively, while the CON and HFD groups with an equivalent volume of distilled water instead.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…Rats in the CON group were fed normal feed, while rats in the other four groups were fed a high-fat diet for 8 continuous weeks. The design of HPC dosage was referred to the previous research studies of Gao et al 30 and Lobo et al 31 Meanwhile, rats in the L-HPC, M-HPC and H-HPC groups were orally given 50, 100 and 200 mg per kg bw of HPC for 8 weeks, respectively, while the CON and HFD groups with an equivalent volume of distilled water instead.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…After administration of procyanidin extract from grape seeds, large amounts of monomer, and dimer procyanidins were accumulated in the cecum and colon (Goodrich & Neilson, 2014). In addition, procyanidins are well‐known for their anti‐inflammatory effects (Lobo et al, 2020). These facts suggest that procyanidins can directly improve colonic intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…PCA was significantly more likely to inhibit the fatty acid synthase (FASN) (92.3%, p < 0.05) and, in general, modulate lipid metabolism (71.0%, p < 0.05) than the other phytochemicals found in the cocoa shell (Figure 3A,B). Studies in animal models have shown an improvement in lipid profile after PCA consumption [20]. Methylxanthines, especially caffeine, showed a significant probability to regulate lipid metabolism (44.6-62.7%, p < 0.05) but with a lower probability of inhibiting FASN (24.9-33.5%, p < 0.05).…”
Section: Protocatechuic Acid Is the Main Contributor To Glucose And L...mentioning
confidence: 99%